(untitled) (Archive of Conferences, 2021)
Leishmaniasis is a tropical disease that is endemic in 98 countries today. Leishmaniasis is a transmissible protozoal disease of humans and animals, the causative agent of which is leishmaniasis, which is transmitted by the bite of carrier scorpion flies. According to the World Health Organization, 350 million people live in areas at risk of leishmaniasis. 600,000 to 1ml per year. Patients with cutaneous leishmaniasis are registered. In addition, 50,000 deaths from visceral leishmaniasis are reported each year. The incidence of cutaneous leishmaniasis has been increasing in recent years